Case History: Controlled Demolition of a Reinforced Concrete Structure in San Sepolcro, Italy - Roberto Folchi (International Society of Explosives Engineers, 1994)
This note deals about the controlled demolition work for the dismantling of an industrial structure in San Seplocro, Italy. The structure to be demolished, the FLOWERS SILOS, consisted in a multilevel reinforced concrete frame supporting r.c. silos and steel silos. This was standing near civil buildings and was adjoining a warehouse that had to be safeguarded for being renewed.